2013
DOI: 10.1371/journal.pone.0054319
|View full text |Cite
|
Sign up to set email alerts
|

High-Throughput Sequencing of microRNAs in Peripheral Blood Mononuclear Cells: Identification of Potential Weight Loss Biomarkers

Abstract: IntroductionMicroRNAs (miRNAs) are being increasingly studied in relation to energy metabolism and body composition homeostasis. Indeed, the quantitative analysis of miRNAs expression in different adiposity conditions may contribute to understand the intimate mechanisms participating in body weight control and to find new biomarkers with diagnostic or prognostic value in obesity management.ObjectiveThe aim of this study was the search for miRNAs in blood cells whose expression could be used as prognostic bioma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
75
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 78 publications
(79 citation statements)
references
References 55 publications
3
75
1
Order By: Relevance
“…43 MiRNAs have also been shown to have utility as clinical predictive biomarkers. 12, 44 Milagro et al investigated peripheral blood miRNA expression among responders and non-responders in a weight-loss trial and reported that two miRNAs (miR-935 and -4772) were upregulated and three miRNAs (miR-223, -224, and -376b) were downregulated in the non-responder group. 44 Our focus on circulating miRNAs in early-mid pregnancy will facilitate the effort to leverage the use of miRNAs in obesity-related mechanistic studies and preventive, diagnostic or therapeutic perinatal applications.…”
Section: Discussionmentioning
confidence: 99%
“…43 MiRNAs have also been shown to have utility as clinical predictive biomarkers. 12, 44 Milagro et al investigated peripheral blood miRNA expression among responders and non-responders in a weight-loss trial and reported that two miRNAs (miR-935 and -4772) were upregulated and three miRNAs (miR-223, -224, and -376b) were downregulated in the non-responder group. 44 Our focus on circulating miRNAs in early-mid pregnancy will facilitate the effort to leverage the use of miRNAs in obesity-related mechanistic studies and preventive, diagnostic or therapeutic perinatal applications.…”
Section: Discussionmentioning
confidence: 99%
“…The target genes of oyster miRNAs were predicted using the miRanda algorithm (score > = 160, free energy< = −25 kcal/mol, http://www.microrna.org/microrna/getDownloads.do) [49].…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, reductions of body fat and serum lipids were related to changes in the methylation status of genes involved in inflammatory response and fatty acid metabolism [99,100]. Furthermore, differential baseline expression of several miRNAs was found between responders and nonresponders to a weight-loss trial that consisted of following an energy-restricted treatment [101]. …”
Section: Diet and Epigenetic Signaturesmentioning
confidence: 99%